Kewajiban Pencatatan Perkawinan Pasca Lahirnya Peraturan Presiden No. 96 Tahun 2018 - Manansyah, Ade; Huda, Misbahul (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2022)
This study focuses on the implications of the existence of a marriage certificate requirement in the process of issuing a child's certificate as stated in Articles 10, 11, 12, 13, 33 and 79 of Presidential Decree No. 96 of 2018 concerning the requirements and procedures for population registration and civil registration. It is just a lack of understanding of regulations, the assumption that recording is only an administrative matter, costs and time are still polemics that are the cause of not registering marriages. Therefore, normative research with a statute approach is carried out by researchers. The primary data in this research is Law no. 23 of 2006 and Presidential Decree No. 96 of 2018. The results show that based on Law no. 23 of 2006 concerning Marriage Registration, the costs and procedures for registering marriages are getting cheaper and more accessible. In addition, the existence of Presidential Regulation No. 96 of 2018 strengthens the obligation to register marriages as mandated by Law no. 23 of 2006 and Law no. 1 of 1974.